2021
DOI: 10.1101/2021.03.26.21254402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attitudes toward COVID-19 illness and COVID-19 vaccination among pregnant women: a cross-sectional multicenter study during August-December 2020

Abstract: Objective: Evaluate pregnant women's attitudes toward COVID-19 illness and vaccination and identify factors associated with vaccine acceptability. Study Design: Cross-sectional survey among pregnant women enrolled in a prospective COVID-19 cohort study in Salt Lake City, UT, Birmingham, AL, and New York, NY, August 9-December 10, 2020. Women were eligible if they were 18-50 years old and <28 weeks of gestation. Upon enrollment, women completed surveys regarding concerns about COVID-19 illness and likelihood… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 20 publications
1
21
1
1
Order By: Relevance
“…40 Another study in the US conducted on 939 pregnant women reported that only 41% of the participants would get a vaccine, and 82.0% of the participants were concerned about vaccine safety for their pregnancy. 41 This study showed that pregnant women and those planning to get pregnant had higher scores of hesitancy regarding taking the vaccine in comparison to women who are not pregnant or not planning to be pregnant. One of the most important factors that increase hesitancy to receive vaccination are problems of trust and hearing or reading about negative events from different sources.…”
Section: Discussionmentioning
confidence: 69%
“…40 Another study in the US conducted on 939 pregnant women reported that only 41% of the participants would get a vaccine, and 82.0% of the participants were concerned about vaccine safety for their pregnancy. 41 This study showed that pregnant women and those planning to get pregnant had higher scores of hesitancy regarding taking the vaccine in comparison to women who are not pregnant or not planning to be pregnant. One of the most important factors that increase hesitancy to receive vaccination are problems of trust and hearing or reading about negative events from different sources.…”
Section: Discussionmentioning
confidence: 69%
“…There were 15,444 participants in all that participated in the study. [16][17][18][19][20][21][22][23][24][25][26][27] Table 1 is based on a review of 12 cross-sectional studies that looked at risk factors and pregnant women's desire to have the SARS-CoV-2 vaccine in various countries. This research revealed variables related to willingness of SARS-CoV-2 vaccination among pregnant women > 35 years, higher school education, sufficient information about the SARS-COV-2 vaccine, high perception, good practice, received influenza vaccine last year and third trimester.…”
Section: Resultsmentioning
confidence: 99%
“…This has motivated widespread hesitancy about recommendation of vaccination to all pregnant women, with governments and professional organizations initially recommending offering vaccination to pregnant women at high risk of either occupational exposure or severe disease 35 and pregnant women reluctant to take up a vaccine offer. 36 In the United States and Israel, where vaccination has been recommended to those at a higher risk, initial data provide a positive signal of safety and efficacy in pregnant women. 33,37,38 Further evidence of a link between SARS-CoV-2 infection and an increased risk of fetal death may motivate prioritization of, and encourage pregnant women to access, vaccination.…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%